Functional and phylogenetic similarity between native and non‐native plant species along an elevational gradient in the central Chilean Andes: No evidence for the preadaptation hypothesis - Anic, Vinka; Mihoč, Maritza; Valencia, Graciela; Reyes‐Bahamonde, Claudia; Bravo, León A.; Sáez, Patricia L.; Pauchard, Aníbal; Cavieres, Lohengrin A. (The Journal of ecology, 2025)
The preadaptation hypothesis proposed by Darwin states that non‐native species phylogenetically close to natives may be successful in the introduced area, as closely related species may exhibit similar adaptations to the environment. In support of this hypothesis, both resident and non‐native plant species have been described as sharing conservative functional traits when subject to habitat filtering, including low leaf area and specific leaf area (SLA). The central Chilean Andes, influenced by a Mediterranean‐type climate, show opposite elevational gradients of water availability and temperature. In this mountain region, low‐elevation drought and high‐elevation cold temperatures may promote a conservative growth strategy in coexisting native and non‐native plant species, thereby reducing the phylogenetic and functional distances between these two species groups. Here, we tested this hypothesis by studying the phylogenetic and functional similarity between co‐occurring native and non‐native plant species along a wide elevational gradient. We measured six leaf functional traits in native (N = 91) and non‐native (N = 26) plant species from roadside habitats at six elevations (from 1200 to 3600 m a.s.l.) in the central Chilean Andes. The traits comprised leaf area, SLA, leaf dry matter content, leaf thickness, and leaf nitrogen and chlorophyll contents. The mean functional and phylogenetic distances of focal non‐native species relative to the native species in the community were calculated. Contrary to our predictions, we found no significant effect of elevation on the functional and phylogenetic distances between native and non‐native plant species. Native species showed reduced SLA in habitats under drought conditions and smaller leaves above the tree line. In contrast, non‐native species exhibited high leaf area values along the entire elevational gradient and high SLA in habitats affected by summer drought. Synthesis. Our study provides novel evidence of the phylogenetic relatedness and functional differentiation between native and non‐native plant species in habitats influenced by summer drought or low‐temperature stress in the central Chilean Andes. In these harsh environments, the acquisitive leaf traits found in non‐native species suggest that the growth strategy of these species could be affected by disturbance and/or the modification of the environment by nurse plants. Successful non‐native species are expected to be similar to natives in the introduced area (preadaptation hypothesis), particularly in harsh environments. We determined the functional and phylogenetic distances between native and non‐native plant species along a wide elevational gradient in the central Chilean Andes. Contrary to our predictions, these distances were unaffected by low‐elevation drought or cold temperatures in high‐Andean habitats.